2008
DOI: 10.1021/bi702343y
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase I-Mediated Translesion Synthesis in RecA-Independent DNA Interstrand Cross-Link Repair in E. coli

Abstract: DNA interstrand cross-links (ICLs) are mainly repaired by the combined action of nucleotide excision repair and homologous recombination in E. coli. Genetic data also suggest the existence of a nucleotide excision repair-dependent, homologous recombination-independent ICL repair pathway. The involvement of translesion synthesis in this pathway has been postulated; however, the molecular mechanism of this pathway is not understood. To examine the role of translesion synthesis in ICL repair, we generated a defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…We prepared a 53-nt length template DNA with a 12-mer oligonucleotide attached via psoralen ICL and placed a four-nucleotide gap between a primer end and a 5’-end of an unhooked strand (Figure 2). Similar types of substrate DNA have been used to study the TLS activity of an ICL 9, 13, 14, 21 . A primer-extension to the attached oligonucleotide by a DNA polymerase results in the production of a 26-nt length fragment.…”
Section: Resultsmentioning
confidence: 99%
“…We prepared a 53-nt length template DNA with a 12-mer oligonucleotide attached via psoralen ICL and placed a four-nucleotide gap between a primer end and a 5’-end of an unhooked strand (Figure 2). Similar types of substrate DNA have been used to study the TLS activity of an ICL 9, 13, 14, 21 . A primer-extension to the attached oligonucleotide by a DNA polymerase results in the production of a 26-nt length fragment.…”
Section: Resultsmentioning
confidence: 99%
“…3Aand 3B) (23). The 74-mer/12-mer was hybridized to a complementary upstream 36-mer or 22-mer, to generate either a nicked or gapped DNA substrate (23). …”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, the cross-linked substrate is well separated from the non-cross-linked substrate. Typically, less than 0.3 % of the substrate was non-cross-linked (23). For the undamaged substrate, a 32 P-labeled 22-mer primer was annealed to the 74-mer template, or a 32 P- labeled 18-mer primer was annealed to a 31-mer template.…”
Section: Methodsmentioning
confidence: 99%
“…Zietlow and Bessho [2008] showed that Pol I was able to bypass a psoralen ICL, preferentially incorporating a dAMP opposite the adducted thymine. This bypass was however very inefficient (below 1%), and it remains to be determined if the reaction could rendered more efficient by reducing the amount of dsDNA around the ICL.…”
Section: Pol I Pol Ii and Pol Iv Have Been Implicated In Icl Repairmentioning
confidence: 99%